On the lattice dilation of palladium nanoparticles and a new methodology for the quantification of interstitials - Ciapina, Eduardo G. [UNESP]; dos Santos, Monica L. [UNESP]; Santos, Rayana M.I.S. [UNESP]; Palombarini, Julio [UNESP]; Almeida Júnior, Osvaldo P. [UNESP]; Santana, Jéssica C.C. de Castro; Modesto, Diego A.; Lanfredi, Alexandre J.C.; Santos, Sydney F. (Elsevier, 2021)
In contrast to the expected behavior for metallic nanoparticles (NPs) where a contraction of the lattice parameter occurs as the crystal size decreases, palladium NPs experience both lattice contraction and dilation. Such dual behavior has not been discussed in detail so far but it is of paramount importance given Pd is widely used in catalysis, electrocatalysis, gas sensors, and many other areas, and all these applications are strongly affected by structural change at the NP surface. Herein, we address the issue investigating both lattice contraction and dilation of Pd NPs synthesized by chemical reduction and also by compiling several results already published in the literature. It was found that when the synthesis is carried out in the absence of a substrate, dilation of the unit cell was detected; in contrast, if the synthesis is carried out in the presence of a substrate (carbon and RuO2), lattice contraction is observed. Lattice dilation was ascribed by the incorporation of interstitial atoms, such as H, C, O, which is suppressed on supported catalysts likely by a spillover effect from the metallic phase to the substrate, thus yielding to lattice contraction. Furthermore, we propose a new methodology to assess the total variation of the lattice parameter in the case of lattice dilation taking into consideration the expected contracted values for nanosized particles. To illustrate the importance of such new approach, it was possible to show a particle-size dependence of the carbon solubility on Pd nanostructures based on literature data.
Keywords: Chemical synthesis; Fuel cells; Hydrogen absorbing materials; Metals and alloys; Nanostructured materials; X-ray diffraction